Patriarcado e violência: desemprego masculino e reviravolta feminina nos papéis sociais de gênero: Vitória-ES (2002-2010) - Ferrari, Alex Silva (2016)
Since the 1970s the Brazilian feminist movement sought to draw attention to cases of violence against women. Among them, the most common type is the domestic violence. Studies on these cases show the complex relations involved in the processes that generate physical, moral and psychological aggression, highlighting the importance of the male and female social role in the dynamics of the relationships of those who were involved in cases of domestic violence. This work aims to analyze the male unemployment in the incidents registered in the Specialized Police Department in Care for Women in the city of Vitória, state of Espírito Santo(DEAM/Vitória). Therefore, it is understood that the work, in contemporary times, is a key point in the construction of male identity. Also, it was used as a legitimizing tool of man's power over the family, especially concerning the woman, in the process of the construction of gender roles. In this researchmale unemployment is seen as a failure in the social role of men, which leads to sociocultural conflicts, what leads, in the men’s imaginary, to a form of castration, loss of power and vulnerability. In this workit is argued that, due to the strong presence of violence in the men's social education, which is also marked by no demonstration of feelings and vulnerability, this is also a tool that can be used by unemployed men against women, in an attempt to re-establish a position of superiority through the objectification of the victims by means of violence.